Współczesne Poglądy na Mechanizm Zniszczenia - Krzemiński, J. (Engineering Transactions, 1972)
Various types of fracture mechanisms arc critically reviewed in the paper, particular attention being paid to the brittle fracture. Application of rate processes to the construction of new fracture hypotheses is demonstrated.